"Ele é meu amigo": comunicação, consumo de smartphones e o envelhecimento conectado - Corrêa, Luciana da Silva (2018)
Based on the theoretical triad that encompasses the aging studies, cyberculture, and the study of the interfaces of communications and consumer, this dissertation takes smartphones as an empirical object to discuss the consumption and appropriation of intelligent devices in everyday life of women aged 60 to 80 years old, of middle and upper middle classes, living in the city of São Paulo. Based on the hypothesis that the smartphone is a facilitator of the connections of these people with family and friends, we see that the smartphone stands out as a means of communication for this public. Understanding that, in a contemporary perspective, the binomial elderly and intelligent technologies can no longer be considered paradoxical, our study intends to bring to light the cultural meanings attributed to smartphones and the role the played by the elderly women in the consumption practices associated with the artifact. In this sense, we understand that one of the forms of aging that mark the twenty-first century presupposes the existence of what we have called in this dissertation as a "connected old age". Our research was developed in three stages - bibliographical review; online survey and personal interviews; and critical analysis. Cultural and reflexive critical analysis concludes that old age and technology can effectively walk side by side and that the incorporation or not of intelligent devices in the daily life of the elderly is not a matter exclusively tied to chronological age, but is based on variables such as personal and professional history; lifestyle; personal interests and aspirations.